Dynamics of the Pacific oyster pathobiota during mortality episodes in Europe assessed by 16S rRNA gene profiling and a new target enrichment next‐generation sequencing strategy. (31st July 2019) - Lasa, Aide; di Cesare, Andrea; Tassistro, Giovanni; Borello, Alessio; Gualdi, Stefano; Furones, Dolors; Carrasco, Noelia; Cheslett, Deborah; Brechon, Amanda; Paillard, Christine; Bidault, Adeline; Pernet, Fabrice; et al.
Summary: Infectious agents such as the bacteria Vibrio aestuarianus or Ostreid herpesvirus 1 have been repeatedly associated with dramatic disease outbreaks of Crassostrea gigas beds in Europe. Beside roles played by these pathogens, microbial infections in C . gigas may derive from the contribution of a larger number of microorganisms than previously thought, according to an emerging view supporting the polymicrobial nature of bivalve diseases. In this study, the microbial communities associated with a large number of C . gigas samples collected during recurrent mortality episodes at different European sites were investigated by real‐time PCR and 16SrRNA gene‐based microbial profiling. A new target enrichment next‐generation sequencing protocol for selective capturing of 884 phylogenetic and virulence markers of the potential microbial pathogenic community in oyster tissue was developed allowing high taxonomic resolution analysis of the bivalve pathobiota. Comparative analysis of contrasting C . gigas samples conducted using these methods revealed that oyster experiencing mortality outbreaks displayed signs of microbiota disruption associated with the presence of previously undetected potential pathogenic microbial species mostly belonging to genus Vibrio and Arcobacter . The role of these species and their consortia should be targeted by future studies aiming to shed light on mechanisms underlying polymicrobial infections in C . gigas .